The Information Content of Sustainability Reporting of Companies in Iran's Capital Market with an Emphasis on its Quality - Shahnaz Mashayekh; Mahnaz Beizaeinezhad (Iranian Journal of Accounting, Auditing & Finance)
The literature on corporate sustainability performance indicates that researchers have often focused on the individual dimensions of corporate sustainability performance. However, few studies have comprehensively measured the company's sustainability performance. In fact, many studies overlook the quality of sustainability reports, which can contain more information content. Therefore, this study investigates the information content of the sustainability reporting quality of listed companies in Iran. Examining 199 companies from 2014 to 2022, the study uses panel data analysis in EViews 9 software. The quality of sustainability reporting is measured using the reliability index by Sebrina and the Ohlson market value model is used to determine the information content. Findings indicate that the quality of sustainability reporting has information content but has not increased the information content of financial statements. This may be due to the novelty of sustainability reporting in Iranian companies. It is suggested that legislators conduct necessary investigations regarding the cost-benefit of making companies' sustainability reporting discretionary or mandatory.